A "Signal On" Photoelectrochemical Biosensor Based on Bismuth@N, O‐Codoped‐Carbon Core–Shell Nanohybrids for Ultrasensitive Detection of Telomerase in HeLa Cells. Issue 15 (11th January 2018) - Liu, Shanshan; Zhao, Shulin; Tu, Wenwen; Wang, Xiaoying; Wang, Xiao; Bao, Jianchun; Wang, Yu; Han, Min; Dai, Zhihui
Abstract: Invited for the cover of this issue is the group of Min Han and Zhihui Dai at the Nanjing Normal University. Read the full text of the article at 10.1002/chem.201704251 . Abstract : " This study confirms the potential of core–shell NHs as an excellent photoactive material for fabricating various biological and biomedical devices ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3677 ff. (DOI:10.1002/chem.201704251 ).